2021
DOI: 10.12688/f1000research.75532.1
|View full text |Cite
|
Sign up to set email alerts
|

Availability and use of technology for e-learning: to what extent do these impact Bangladeshi university students? A cross-sectional study

Abstract: Background: E-learning is making education globally and conveniently attainable with the deliverance of advanced technology. However, this mode of academia is still not commonly practiced locally. Thus, the study aimed to investigate technological availability, usability, and association to university students' perceived stress due to e-learning curriculum. Methods: A cross-sectional study commenced among Bangladeshi university students enrolled in the e-learning curriculum. A total of 1162 university students… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 60 publications
(91 reference statements)
1
2
0
Order By: Relevance
“…The second hypothesis aimed to ascertain the extent to which the availability and limitations of facilities impacted satisfaction levels. The findings positively affirmed this association, albeit to a modest degree, which is consistent with the studies undertaken by Hasan et al [77] and Cho and Tobias [78]. Consequently, the outcomes accentuated the merits of a well-structured class system, robust supervision, and meticulous feedback monitoring in ameliorating challenges and fostering self-reliance among students.…”
Section: Discussionsupporting
confidence: 85%
“…The second hypothesis aimed to ascertain the extent to which the availability and limitations of facilities impacted satisfaction levels. The findings positively affirmed this association, albeit to a modest degree, which is consistent with the studies undertaken by Hasan et al [77] and Cho and Tobias [78]. Consequently, the outcomes accentuated the merits of a well-structured class system, robust supervision, and meticulous feedback monitoring in ameliorating challenges and fostering self-reliance among students.…”
Section: Discussionsupporting
confidence: 85%
“…The possible reason could be as they were more likely to expose to distance learning and technology based service usability. [44][45][46][47] A similar study measuring nursing students' readiness to use telenursing was carried out in Poland. 48 Amazingly, 69.49% of the students reported that they would be very likely to include telenursing in their course curriculum.…”
Section: Discussionmentioning
confidence: 99%
“…The possible reason could be as they were more likely to expose to distance learning and technology based service usability. [42][43][44][45] A similar study measuring nursing students' readiness to use telenursing was carried out in Poland. 46 Amazingly, 69.49% of the students reported that they would be very likely to include telenursing in their course curriculum.…”
Section: Discussionmentioning
confidence: 99%